“I came home. Is this home?”: Post-Brexit Migration and Emotions in Years and Years - Mora-Ramírez, Pedro (2024)
The rise of border audiovisual productions in recent decades is a possible conclusion to the difficulties imposed by border control policies. The BBC TV fictional series, Years and Years (2019), presents how Brexit causes vulnerabilities by exacerbating racial differences, such as the persecution of refugees. Because of the complication in border transits, Years and Years (2019) reconsiders the role of borders to claim that they are fundamental in inciting fear, hate, and vulnerabilities. Drawing on the scholarship by Postcolonial and Affect critics such as Caroline Koegler, Malreddy and Tribucke, and Ahmed, I analyse critically episodes 4 and 5 of the series. In this paper, I propose that a study of fear, pain, and hope promotes action-taking in the series' characters. Secondly, I reflect on how Brexit unveils colonial vestiges reflected in imperial nostalgia. Finally, I suggest that imperial nostalgia transforms into familial nostalgia and causes individuals to verbalize hatred toward what unsettles them.